Internal Migration in Mexico in the year 2000. - Pimienta Lastra, Rodrigo; Vera Bolaños, Marta; Shea, Michael; Gutiérrez Cárdenas, Elena Marcia (Facultad de Trabajo Social, Universidad Autónoma de Nuevo León, 2011)
This study, based on the Census sample of 2000, sought to identify permanent internal migratory flows: people settled in a geographical entity different from that in which they were born. The aim was to establish the volume of migration and the characteristics of the localities (birth and residence) and, at the same time, provide interpretations of these phenomena within some established theoretical frameworks. Methodologically, the principal flows of migration between states of the Republic were established and correlated with the size of the localities to which migrants are attracted. It was found that, the age groups and genders of migrants are reinterpreted, as are their choice of destinations, to give a picture of internal migration different from that suggested in general models, especially those originating in the first world. The role of women in migration in Mexico seems particularly important. A new interpretation of the migration of children is suggested.